Izklop trifaznega kratkostičnega toka s tripolnim nizkonapetostnim odklopnikom - Bizjak, Martin (Informacije MIDEM, 2009)
Circuite breakers are switching apparatus used to break short-circuit currents. Low voltage circuit breakers operate in short-circuit conditions by applying method of current limitation in order to reduce the magnitude and theduration of let-through current. The break is possible at current zero. Therapid increase of voltage between breaker's terminals, which forces the current rapidly toward zero, is provoked by the lengthening of arc column between opening contacts and forming of an arc loop, which finally enters the arc chutes, reaching voltage comparable to the source voltage. The waveform of voltage increase is typical for breaking events regardless of circuit conditions or even of the methods of current breaking, either by electromechanical circuit breaker or by melting fuse. In contrary to breaking of single-phase short-circuit current, at three-phase short-circuit current, at three-phase short-circuit breaking event the voltage waveform of each particular phase does not always follow the typical single-phase one. The sum of influences of currents in the adjacent phases can result on the arcof particular phase in the sense to decelerate them on its way to arc chutes and the current limiting effect can be substantially delayed. Irregardless of uniform distribution of phase angle difference between phases of three-phase currents it is found out, that the conditions of break are harder for circuit-breaker at some specific phase angles of short-circuit event.
Keywords: izmenični tok; kratkostični tok; odklopniki; trifazni tok